The Use of Moringa Seeds and Alum to Improve the Quality of Well Water into Drinking Water - Bambang Sugiarto; Sephia Lita Acitya Putri; Alvina Damayanti; Retno Dwi Nyamiati (Jurnal Teknik Kimia, 2026)
Water is a basic need of living things that is very important to maintain its quality so that it does not cause problems. The method that can be used to improve water quality is to carry out the coagulation method using moringa seed coagulant (moringa oleifera) and alum which has been proven to be able to improve the quality of water. Both coagulants can reduce the following parameters, turbidity by reducing TSD, neutralizing pH, reducing dissolved metal levels, color, and reducing microorganisms contained in it such as E-coli bacteria and total coliform. The results of this study indicate that the two coagulants can reduce the parameter values of TDS, turbidity, iron content, E-coli, color, and pH in the sample water to be below the maximum limit or in accordance with drinking water quality standards, but the nitrate parameter is not yet below the maximum level. The optimum concentration to improve the quality of well water into drinking water is 2.5 ppm with an optimum residence time of 4 weeks.